(untitled) (Journal of Engineering, 2016)
Partial shading is one of the problems that affects the power production and the efficiency of photovoltaic module. A series of experimental work have been done of partial shading of monocrystalline PV module; 50W, Isc: 3.1A, Voc: 22V with 36 cells in series is achieved. Non-linear power output responses of the module are observed by applying various cases of partial shading (vertical and horizontal shading of solar cells in the module). Shading a single cell (corner cell) has the greatest impact on output energy. Horizontal shading or vertical shading reduced the power from 41W to 18W at constant solar radiation 1000W/m2 and steady state condition. Vertical blocking a column of cells (9 cells) in a module reduces the power from 41W to 18W (53% power reduction); while, blocking one or two cell in the row reduces the power from 41 W to 18W (53% power reduction). Shading three or four cells in the same row reduces the power from 41W to 1W or 0.006W (94% power reduction). A complete Matlab / Simulink model are achieved to simulate the effect of partial shading on power output of module. It is found that shading a single cell reduces the power from 50 W to 25 W (50%) using Matlab/Simulink model. Comparisons have been made between the I-V and P-V characteristic curves from the simulation with the practical (experimental) curves. The results showed that the percentage of error between the Simulink results and the corresponding experimental measurement are 22% without shading effect and, 32% with partial shading.